Blending Wabi-Sabi Principles With Minahasan Cultural Identity In The Design Of The City Library And Learning Center Manado - Gabriela Tabita Thambas; Cynthia Erlin Virgin Wuisang; Pingkan Peggy Egam (MEDIA MATRASAIN, 2026)
ABSTRACT Manado is currently experiencing a demographic bonus characterized by a growing proportion of productive-age population. This demographic condition presents an important momentum for the development of environments that support intellectual growth, creativity, and knowledge exchange. However, urban activities in Manado are largely concentrated in commercial spaces that are predominantly consumption-oriented. While these spaces function as popular gathering places, they are not designed to support meaningful learning processes or knowledge-oriented activities. At the same time, contemporary learning has evolved beyond conventional classroom settings and increasingly occurs in flexible and informal environments, including public spaces. Despite this shift, Manado still lacks adequate public facilities that intentionally nurture learning processes within the urban environment. This study proposes the design of a City Library and Learning Center in Manado as a public learning infrastructure that responds to this urban gap. The design integrates Wabi-Sabi architectural principles, which emphasize simplicity, natural materials, and harmony with nature, while also incorporating Minahasan cultural identity into the architectural expression. Through literature study, precedent analysis, and site analysis, the design explores spatial strategies that balance quiet learning environments with collaborative and interactive spaces. The resulting architectural proposal aims to create a public learning environment that supports both focused study and social knowledge exchange while reinforcing the cultural identity of Manado.  Keywords: Library, Learning Center, Wabi-Sabi, Minahasan Culture, Demographic Bonus, Manado.   ABSTRAK Manado saat ini sedang mengalami bonus demografi yang ditandai dengan meningkatnya proporsi penduduk usia produktif. Kondisi demografis ini menghadirkan momentum penting untuk pengembangan lingkungan yang mendukung pertumbuhan intelektual, kreativitas, dan pertukaran pengetahuan. Namun, aktivitas perkotaan di Manado sebagian besar terkonsentrasi di ruang komersial yang didominasi oleh orientasi konsumsi. Meskipun ruang-ruang ini berfungsi sebagai tempat berkumpul yang populer, mereka tidak dirancang untuk mendukung proses belajar yang bermakna atau aktivitas yang berfokus pada pengetahuan. Di sisi lain, pembelajaran kontemporer telah berkembang melampaui pengaturan kelas konvensional dan semakin terjadi di lingkungan yang fleksibel dan informal, termasuk ruang publik. Meski ada pergeseran ini, Manado masih kekurangan fasilitas publik yang memadai yang secara sengaja mendukung proses pembelajaran dalam lingkungan perkotaan. Studi ini mengusulkan desain Perpustakaan dan Pusat Belajar Kota di Manado sebagai infrastruktur pembelajaran publik yang menanggapi kesenjangan perkotaan ini. Desainnya mengintegrasikan prinsip arsitektur Wabi-Sabi, yang menekankan kesederhanaan, material alami, dan harmoni dengan alam, sambil juga memasukkan identitas budaya Minahasa ke dalam ekspresi arsitektural. Melalui studi literatur, analisis preseden, dan analisis lokasi, desain ini mengeksplor strategi ruang yang menyeimbangkan lingkungan belajar yang tenang dengan ruang kolaboratif dan interaktif. Proposal arsitektural yang dihasilkan bertujuan untuk menciptakan lingkungan belajar publik yang mendukung baik studi fokus maupun pertukaran pengetahuan sosial, sambil memperkuat identitas budaya Manado.  Keywords: Perpustakaan, Pusat Belajar, Wabi-Sabi, Budaya Minahasa, Bonus Demografi, Manado